2014
DOI: 10.1590/s1517-70762014000200002
|View full text |Cite
|
Sign up to set email alerts
|

Cimentos Portland aditivados com arenito zeolítico com propriedades pozolânicas

Abstract: O uso adequado de pozolanas possibilita a produção de cimentos especiais, de menor custo de fabricação e de maior durabilidade que os correspondentes sem adição. O emprego dessas adições minerais possibilita ganhos significativos em termos de produtividade e uma extensão da vida útil dos equipamentos de produção e da própria jazida de calcário, também ajudando na diminuição de CO2 lançado na atmosfera.As zeólitas têm sido utilizadas como material pozolânico em misturas com "terras vulcânicas" e água nas constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…Apresentam origem sedimentar, e por isso, tendem a ser depósitos volumosos e com grande potencial econômico devido aos baixos custos e facilidade de exploração [41]. Os estudos relacionados com as aplicações do mineral zeolítico provenientes desses jazimentos têm mostrado resultados altamente promissores quanto ao seu uso na agricultura [42][43], adsorção de metais pesados e tratamento de efluentes industriais [44][45] e na construção civil [46][47][48].…”
Section: Argilas Especiaisunclassified
“…Apresentam origem sedimentar, e por isso, tendem a ser depósitos volumosos e com grande potencial econômico devido aos baixos custos e facilidade de exploração [41]. Os estudos relacionados com as aplicações do mineral zeolítico provenientes desses jazimentos têm mostrado resultados altamente promissores quanto ao seu uso na agricultura [42][43], adsorção de metais pesados e tratamento de efluentes industriais [44][45] e na construção civil [46][47][48].…”
Section: Argilas Especiaisunclassified
“…Besides influencing factors such as degree of crystallinity and variations in the orientation of crystals while preparing the samples, the variation of the intensity of portlandite peaks by DRX for the study of pozzolans is related with their amount in the cementitious composite [19]. Voglis et al [20], Antiohos et al [21], Cabral [22], Dantas [23], Picanço et al [24], Vaitkevicius et al [25], Gómez-Zamorano et al [26], AboEl-Enein et al [27] and Silva [28] also used the reasoning of comparing the intensity of peaks for studying pozzolans, as other works from the research group that created this paper also did. Publications of Gobbi [29], Raisdorfer [30], Medeiros et al [31] and Medeiros et al [32] and Hoppe Filho et al [33] are examples of this.…”
Section: Study About Alkaline Reserve Using Xrdmentioning
confidence: 99%
“…Musyoka et al 198 reported on the conversion of South African clays into high quality zeolites. Both XRF and XRD analyses were used by Picanco et al 200 to characterise Portland cement activated with pozzolanic zeolite sandstone from the Parnaiba Basin, Brazil. The inuence of pH on the membrane behaviour of bentonite amended clay from Fa, China was investigated by Tang et al 199 using the techniques of XRF, XRD and SEM to measure membrane properties.…”
Section: Industrial Minerals and Consequences From Mining Activitymentioning
confidence: 99%
“…The relevance of this work is the use of this material as liners for landll sites to provide a barrier against the migration of contaminants. Both XRF and XRD analyses were used by Picanco et al 200 to characterise Portland cement activated with pozzolanic zeolite sandstone from the Parnaiba Basin, Brazil. This study was designed to evaluate the ideal amount of thermally activated zeolitic sandstone to be incorporated into the Portland cement to improve its mechanical and mineralogical properties (10% was recommended).…”
Section: Industrial Minerals and Consequences From Mining Activitymentioning
confidence: 99%